The Second Synod of the Wloclawek’s Diocese by Bishop Hieronim Rozrażewski in 1589 - KRUCKI, ŁUKASZ (Prawo Kanoniczne, 2014)
Bishop Hieronim Rozrażewski was chairing the Second Synod of the Wloclawek’s Diocese in September 22nd, 1589. During these deliberations, the following issues had been discussed: the defense of the Catholic faith, the privileges and obligations of the clergy, the administrative directives concerning the offices, the sacramental service, the Divine worship, the times and holy places. It’s worth mentioning that the reform of the religious life and the issue of the Catholic teaching and improvements in education had been discussed as well. The statutes which had been accepted by the Synod, considered Bishop Hieronim Rozrażewski, to be one of the most active advocates of the Tridentine reform in Poland.